TRANSFORMING MSMES TO A DIGITAL ECONOMY: BANK MANDIRI'S ROLE THROUGH QRIS AS A FINANCIAL INCLUSION INSTRUMENT IN KETIMANG VILLAGE - Paduppai, Andi Mardiana; Ningrum, Titin Sekarjati; Ramadhani, Nur Rochma; Kurniawa, Danang Dwi (Antis-publisher, 2026)
Objective: This study examines the contribution of QRIS to the digital transformation of MSMEs in Ketimang Village through collaboration with Bank Mandiri and the support of the KKN program. Method: A descriptive qualitative method was employed using observation, interviews, documentation, and questionnaires. Results: The findings indicate that QRIS positively impacts transaction efficiency (4.55), financial transparency (4.46), and digital market expansion (4.34). Bank Mandiri plays a vital role in strengthening MSME competitiveness (4.48), while the KKN program effectively enhances digital literacy and provides technical assistance (4.51). Product innovation is also considered important, with a score of 4.45. Challenges remain in terms of limited capital (4.07) and insufficient digital literacy (4.45). The highest-rated aspect is stakeholder synergy (4.70), highlighting that multiparty collaboration is fundamental for establishing an inclusive and sustainable MSME ecosystem. Novelty: The digital transformation of MSMEs through QRIS can be optimized through continuous improvements in digital literacy, better access to financing, and sustained collaborative support among stakeholders.